MERITOCRACY VS. NEPOTISM: EVALUATING RECRUITMENT/SELECTION POLICIES AND ORGANIZATIONAL OUTCOMES IN NIGERIAN PUBLIC UNIVERSITIES (2018–2025) - Onyeiwu, Emmanuel Anayo (African Journal of Social and Behavioural Sciences, 2025)
This study examined Meritocracy vs. Nepotism: evaluating recruitment/selection policies and organizational outcomes in Nigerian public universities (2018–2025). In an effort to achieve the objective of the study, the researcher's employee survey research design and questionnaires were the primary data collection tool. The data collected were presented in tables and analysed using simple percentages and Pearson product-moment correlation coefficients. The population of this study is made up of the entire permanent staff of Imo State University, from where 262 respondents were sampled using a simple random sampling technique. However, only 240 copies of the questionnaire were returned and used. The result indicated that there is a significant relationship between recruitment/selection policy and the level of turnover in Nigerian organizations; recruitment/selection policy affects productivity in Nigerian organizations, and there is a significant impact of recruitment/selection policy on industrial peace and harmony in Nigerian organizations. Based on the findings, it was recommended that organizations seeking employee retention should always adopt an internal recruitment/selection policy so as to reduce the rate of job turnover. Furthermore, organizations that want to achieve high productivity and high output should use external recruitment/selection policy.